Perhitungan Harga Pokok Produksi Dengan Metode Harga Pokok Proses Pada PT. Persada - Dian Indah Sari (Universitas Bina Sarana Informatika, 2018)
Abstract-Process processing in manufacturing companies can be divided into two major groups namely the production process by order and mass production process. This study aims to calculate the cost of production using the cost of process method at PT.Persada. The research method used in this research, among others, Field Research is to obtain data by coming directly to the company. Field research is conducted by interviewing the company's head and part directly involved with the research topic. Literature study is to obtain data by means of literature studies obtained from books and journals to obtain theories related to research topics. Data analysis is after obtaining the data then performed data analysis by calculating unit ekulivalensi and report cost of goods production. Based on the above discussion it can be concluded as follows: PT. Persada uses the calculation of the cost of production is still simple. Because in the calculation of the cost of production using the rate of market price changes. Calculation of cost of goods manufactured by the cost method of the process as follows: Total production cost assembly department is Rp 39.700.000.Number of production costs of the department of settlement is Rp 46.900.000.Total production costs as a whole is Rp 85.600.000.Apabila PT Persada using the method the cost of the process in calculating the cost of production will result in greater profits. Keywords: Cost of Production, Cost of Process